Centres and Peripheries in Gender History: A Historiographical Review - Dialeti, Androniki (Historein, 2025)
This article has two purposes. Firstly, it examines recent historiographical overviews that mostly discuss “peripheral” or “national”/“regional” historiographical traditions, to detect current aspirations, frustrations and challenges in respect of how academic centres, peripheries and hierarchies are constructed in gender history today. Secondly, it discusses the profile of four international journals dedicated to women’s and gender history to examine how historiographical centres and peripheries have been shaped through their pages in the last decade (2011–2020).